2018
DOI: 10.1044/2018_ajslp-odc11-17-0185
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Strategies for Speech-Language Pathologists Using the Lidcombe Program for Early Stuttering

Abstract: Purpose The Lidcombe program is a treatment for preschool-age children who stutter. Studies indicate that its implementation is not always straightforward. In this study, challenges that parents and speech-language pathologists (SLPs) encounter when implementing the Lidcombe program were identified, and strategies to address them were sought. Method In Part 1, Lidcombe program treatment challenges were determined from 4 sources. In Part 2, 7 SLPs with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The scientific beauty of this course preceded by a comprehensive slide presentation is that this course has well defined vision and mission, values and goals [2] and rightly authenticated by trainees in terms of their success stories [38]. The PWS face a variety of challenges linked with worsening stuttering [43] were very well addressed individually and various techniques that help resolve stuttering were highlighted and the participants were guided to practice at home with family, friends, the Will Club Members and others. Some of the same challenges associated with stuttering were also discussed during addressing various methods, stages/phases of treatment possibly may have further consolidated the memory and knowledge of the participants for correctly practicing these techniques but this training perspective gave a sense of repetition of ideas scattered throughout this paper.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific beauty of this course preceded by a comprehensive slide presentation is that this course has well defined vision and mission, values and goals [2] and rightly authenticated by trainees in terms of their success stories [38]. The PWS face a variety of challenges linked with worsening stuttering [43] were very well addressed individually and various techniques that help resolve stuttering were highlighted and the participants were guided to practice at home with family, friends, the Will Club Members and others. Some of the same challenges associated with stuttering were also discussed during addressing various methods, stages/phases of treatment possibly may have further consolidated the memory and knowledge of the participants for correctly practicing these techniques but this training perspective gave a sense of repetition of ideas scattered throughout this paper.…”
Section: Discussionmentioning
confidence: 99%
“…None of these, however, are conclusive to predict treatment duration or ease of treatment implementation for a PCWS; that is, they do not apply to all PCWS. Goodhue et al [27] and Van Eerdenbrugh et al [37] reported child and family challenges such as PCWS with a (twin) sibling who stutters, perfectionist or sensitive PCWS, a family's busy lifestyle, parents with a learning disorder, weaker intellectual capabilities, feelings of anxiety, a depression, a troublesome relationship with their PCWS, a parent who is stuttering or a divorced family situation. It is important to realize however, that Van Eerdenbrugh et al…”
Section: Mini-kids Program Also Focuses On Dealing With the Left-over...mentioning
confidence: 99%
“…Family attributes were lifestyle of a family, ability to steer a conversation with the PCWS, playing habits, stuttering of the parent who is implementing the treatment, stuttering of someone in the family, learning disorder, weaker intellectual capabilities, feelings of anxiety, depression, troublesome relationship with the PCWS and a divorced family situation. These attributes were mentioned either as challenges [37] , as obstacles or benefits [27] , or were reported in association with stuttering recovery [e.g., 60, 61, 62] , treatment duration or treatment outcome [e.g., 52,53,54,55] or drop-out [e.g. , 54] .…”
Section: Construction Of the Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are no qualitative studies investigating the implementation process by parents and children according to the results of this review. However, the fact that a qualitative investiga-tion in Australia revealed a number of challenges faced by speech and language therapists and parents [49] suggests possible challenges implementing the Lidcombe Program in non-native English-speaking countries, underscoring the need for more qualitative explorations outside of native English-speaking countries.…”
Section: Study Designs Of the Studies Conducted In Non-native English...mentioning
confidence: 99%